The colonization of the Puna and Atacama Biogeographic Province by sister clades of Psectrascelis (Coleoptera: Tenebrionidae): Synchronous expansion without spatial overlap. (7th May 2021) - Zúñiga‐Reinoso, Alvaro; Ritter, Benedikt; Predel, Reinhard
Abstract: Aim: We investigated the biogeographic pattern of the species‐rich genus Psectrascelis (Coleoptera: Tenebrionidae) in the Central Andes and the Chilean Atacama Desert as an example for insect evolution in such a geologically and climatically highly dynamic arid region. The main aim was to test two alternative hypotheses about the main drivers of diversification of biotas from deserts in the region: Andean uplift versus Pleistocene fragmentation/dispersal. Location: South America, Central Andes, Atacama Desert. Taxon: Psectrascelis (Coleoptera: Tenebrionidae). Methods: A phylogenetic tree based on cytochrome oxidase I, 16S and Wg genes was prepared for multiple individuals from 36 populations of the region representing 14 species or subspecies. Divergence times, ancestral ranges and biogeographic events that may have led to the current distribution and species diversity were estimated. Results: The first split within the genus is not directly related to the Andean uplift but began at the time of global cooling at ~3.5 Ma, when the Andes had already reached their current altitude. Further differentiations of Psectrascelis lineages were mostly caused by common and more global drivers resulting in major clusters of diversifications at ~2.6–2.2 Ma, ~1.3–0.7 Ma and several subsequent events during the mid‐ to late Quaternary. Today, the two main clades of Psectrascelis almost meet each other after presumably synchronous range expansions along the Western Cordillera. Main conclusions: Diversification of Psectrascelis has primarily been affected by global climate changes since the mid‐Pliocene and has involved multiple vicariance and jump dispersal events. We hypothesize that jump dispersal events have occasionally been accompanied by adaptation to stronger aridity, which paved the way for range expansion into previously unsuitable habitats and eventually led to synchronous colonizations without spatial overlap along different isohyets in the Western Cordillera during the late Pleistocene.